2014
DOI: 10.1007/s40477-014-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous bilateral segmental testicular infarction: multi-parametric ultrasound imaging with grey-scale ultrasound, Doppler ultrasound, contrast-enhanced ultrasound (CEUS) and real-time tissue elastography (RTE)

Abstract: Segmental testicular infarction is a rare cause of acute scrotal pain. The appearances on grey-scale sonography are often indistinguishable from that of a testicular tumour, resulting in unnecessary orchiectomy. We report a case of acute bilateral testicular infarction, of unknown etiology, which was conservatively managed to resolution following a confident diagnosis achieved with the aid of contrast-enhanced ultrasound (CEUS) and real-time tissue elastography (RTE) along with conventional grey-scale and Dopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Only small studies or case reports for single entities include the combination of strain elastography and contrast-enhanced US (11)(12)(13)(14). The aim of this study was to evaluate the diagnostic accuracy of multiparametric US consisting of grayscale US, color Doppler US, strain elastography, and contrast-enhanced US in the assessment of intratesticular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Only small studies or case reports for single entities include the combination of strain elastography and contrast-enhanced US (11)(12)(13)(14). The aim of this study was to evaluate the diagnostic accuracy of multiparametric US consisting of grayscale US, color Doppler US, strain elastography, and contrast-enhanced US in the assessment of intratesticular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…6). Focal lesions can often be recognized as harder than the 1198 Andrology, 2016Andrology, , 4, 1193Andrology, -1203 surrounding testicular tissue, with some important exceptions reported with hematomas or mixed fluid lesions (Patel et al, 2014;Yusuf et al, 2015). Normal testis parenchyma is hard, but compared with the even harder solid tumorous tissue, it has a relatively softer appearance, displaying areas of green and light blue (Jedrzejewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Its output include a color‐coded representation (qualitative assessment) of the lesion and a semi‐quantitative characterization by strain ratio, calculated as the ratio of the surrounding parenchyma to the lesions and providing a measure of lesion stiffness. SE has been successfully used in the evaluation of acute scrotal pathology (Shah et al ., 2010; Patel et al ., 2014; Yusuf et al ., 2015). However, to date, only a few studies (Schurich et al ., 2009; Grasso et al ., 2010; Aigner et al ., 2012; Huang & Sidhu, 2012; Patel et al ., 2012; Marsaud et al ., 2015) and just one prospective study (Goddi et al ., 2012) have explored the role of SE in focal testicular lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Significant findings in the present study demonstrated that CEUS + RTE displayed a higher sensitivity and specificity when compared with CEUS or RTE alone, indicating the high diagnostic performance of CEUS + RTE in distinguishing benign from malignant thyroid nodules. The diagnostic performance of CEUS and RTE has been individually assessed by numerous studies (33)(34)(35). On CEUS scans, papillary thyroid carcinoma shows a heterogeneous low enhancement pattern, whereas nodular goiters show an equal enhancement pattern (28).…”
Section: Discussionmentioning
confidence: 99%